2018
DOI: 10.1111/ijau.12127
|View full text |Cite
|
Sign up to set email alerts
|

Entrance requirements to the audit profession within the EU and audit quality

Abstract: This paper examines the relation between the stringency of entrance requirements to the audit profession within the EU and audit quality. Regulators and standard setters generally believe that such entrance requirements have beneficial effects by increasing audit quality. Whether this is indeed the case, however, is an empirical question given that regulations governing the entry to the audit profession are not the product of competitive market forces. We argue that a higher educational degree and longer train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 72 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…On the one hand, the question about the necessary knowledge and skill set of auditors, and hence the appropriate design of CPA exams and education and training, becomes pre‐eminent. The research outcome by Van Linden and Hardies (2018) demonstrated the impact of entrance requirements to the audit profession on audit quality. On the other hand, the question arises as to how audit team composition and communication as well as quality control processes should be designed.…”
mentioning
confidence: 99%
“…On the one hand, the question about the necessary knowledge and skill set of auditors, and hence the appropriate design of CPA exams and education and training, becomes pre‐eminent. The research outcome by Van Linden and Hardies (2018) demonstrated the impact of entrance requirements to the audit profession on audit quality. On the other hand, the question arises as to how audit team composition and communication as well as quality control processes should be designed.…”
mentioning
confidence: 99%